20 Nilai Kehidupan Sebagai Alat Pembentuk Karakter Peserta Didik Melalui Dongeng Cerita Rakyat Dalam Pembelajaran - Margaretha Sri Sukarti (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2013)
Abstract: Character turns desperately need intensive attention in its building. Teachers can build the character of the students through the medium of folklore that contains the values of life in learning. Folklore can be delivered using storytelling methods. As a medium in character education, folklore can provide a variety of value of life as a means of forming the character of students. Folklore can be delivered by teachers when there is a pause in the learning and the ice breacking for lightening saturation during the study. Learners will feel comforted and expected learning outcomes can be achieved more effectively, optimal, and there is a balance of work between the left brain and right brain. Keywords: folklore, fairy tales, values , life.